Exploring the influence of probiotic administration routes on immune responses in atopic march - Fang-Yu Zhang; Chi-Yu Yang; Chien-Hsun Huang; I-Jen Wang; I-Jen Wang; I-Jen Wang; I-Jen Wang (Frontiers in Immunology, 2025)
BackgroundChildren with atopic dermatitis (AD) have a higher likelihood of developing asthma, the so-called atopic march. Previous studies have suggested that probiotics can modulate development of the immune system and atopic disorders. However, the exact mechanisms and whether the route of administration of probiotics has a clinical effect are unknown. Therefore, we conducted this study to investigate whether different routes of administration of probiotics may have different effects.MethodProbiotics Bacteroides plebeius, B. ovatus, 74-B and YCFA-33 were administered to mice via oral and nasal routes for 4 weeks, followed by the induction of AD using ovalbumin (OVA). The condition of the stimulated skin and histology of skin tissues were evaluated. In addition, 3 days of consecutive exposure to OVA (3%) aerosol was used to induce asthma at the end of the AD experiment. Serum immunoglobulin E (IgE), IgG, IL-4, IFN-γ, and TNF-α levels and histological evaluations of lung tissues were assessed after the experiments.ResultThe oral administration of probiotics B. plebeius and B. ovatus may have improved the inflammatory response of OVA-induced asthma. The nasal administration of the probiotics 74-B and YCFA-33 may have alleviated the symptoms of skin redness and itching of OVA-induced atopic dermatitis. These effects may have been due to reduced infiltration of white blood cells in the stimulated skin area and dampened inflammatory responses. In the later asthma model, YCFA-33 administration significantly increased total IgG and IgG1 in serum, reduced OVA-IgE levels and IL-4 levels, decreased neutrophil content and TNF-α expression, and increased IFN-γ levels in lung lavage fluid (p<0.05). These effects may have blocked the progression from AD to asthma pulmonary inflammation.ConclusionB. ovatus had better effects via oral administration while 74-B and YCFA-33 had better effects via nasal administration. Oral administration is not always the best route. Probiotics may mitigate allergic reactions and pulmonary inflammation. These findings could contribute to the development of innovative biomarkers and early interventions for managing asthma and atopic disorders.